Komparasi Hasil Belajar Bahasa Arab Siswa Melalui Metode NHT dan TGT di MTs Ma’arif Jember - Asni Furoidah (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2023)
In the process of teaching and learning, students occupy a very important role in relation to the position of students as subjects. While the teacher is positioned as an object that has a role that is no less important. Learning is very important in the world of education, especially Arabic lessons, because the learning process determines the success of the learning objectives themselves. The success or failure of the teaching and learning process can be seen from the learning outcomes obtained by students. If the learning outcomes achieved by students experience an increase, then the teaching and learning activities that have been carried out can be declared successful. Meanwhile, to produce a quality learning process requires the ability of a teacher to apply learning methods that are appropriate to the conditions and circumstances of students in the classroom. The purpose of this research is to find a comparison of students' Arabic learning outcomes using the Numbered Head Together (NHT) and Team Games Tournament (TGT) methods at MTs Ma'arif Jember. This study uses a qualitative method, with the type of research is a comparative study. While the research approach is in the form of field studies or field research. The results of this research indicate that (1) before using the NHT method, students were less enthusiastic about learning Arabic. This is different after the implementation of this method, that students tend to be more active and enthusiastic in participating in learning in the classroom, so that student learning outcomes in Arabic also increase. (2) Before using the TGT method, students were lazy and less interested in learning Arabic. However, after using the TGT method, students were more interested and their interest increased. Students also enjoy and really enjoy the process of learning Arabic in the classroom. Student learning outcomes also increased. Thus, it can be concluded that of the two methods, it turns out that the TGT method is more effective in improving student learning outcomes compared to the NHT method with a comparison of the average scores, namely TGT = 70.3 and NHT = 61.3.